2016
DOI: 10.1016/j.ccell.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aberrant Epigenetic Networks Mediated by PRMT1 and KDM4C in Acute Myeloid Leukemia

Abstract: SummaryTranscriptional deregulation plays a major role in acute myeloid leukemia, and therefore identification of epigenetic modifying enzymes essential for the maintenance of oncogenic transcription programs holds the key to better understanding of the biology and designing effective therapeutic strategies for the disease. Here we provide experimental evidence for the functional involvement and therapeutic potential of targeting PRMT1, an H4R3 methyltransferase, in various MLL and non-MLL leukemias. PRMT1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(194 citation statements)
references
References 51 publications
10
169
1
1
Order By: Relevance
“…4B). Although the phenotype that we observed upon Jmjd2/Kdm4 depletion was not dependent on deregulated Hoxa9 and Meis1 transcription, Jmjd2c was found to bind to the promoter of Meis1 and Hoxa9, in agreement with Cheung et al (2016) (Supplemental Fig. 3A,B).…”
Section: Jmjd2a and Jmjd2c Bind To H3k4me3-positive Tsss In Mll-af9 Tsupporting
confidence: 76%
See 3 more Smart Citations
“…4B). Although the phenotype that we observed upon Jmjd2/Kdm4 depletion was not dependent on deregulated Hoxa9 and Meis1 transcription, Jmjd2c was found to bind to the promoter of Meis1 and Hoxa9, in agreement with Cheung et al (2016) (Supplemental Fig. 3A,B).…”
Section: Jmjd2a and Jmjd2c Bind To H3k4me3-positive Tsss In Mll-af9 Tsupporting
confidence: 76%
“…This is underscored by the fact that coexpression of Hoxa9 and Meis1 is sufficient to induce transformation of GMPs (Kroon et al 1998;Wang et al 2010). In a recent study published while this work was in preparation, it was reported that Jmjd2c binds to MLL-AF9 and is an essential cofactor for the transcriptional activation of Hoxa9 and Meis1 during leukemic transformation (Cheung et al 2016). According to this study, Jmjd2c is recruited to the TSSs of Hoxa9 and Meis1, where it can demethylate H3K9me3 (Cheung et al 2016).…”
Section: Jmjd2/kdm4 Proteins Are Required For the Survival Of Mll-af9mentioning
confidence: 97%
See 2 more Smart Citations
“…For example, PRMT1 is necessary for leukemic transformation, which requires co-recruitment of KDM4C, an H3K9 demethylase. 75,104 Lysine demethylases Histone methylation is also dynamically controlled by histone/ protein lysine demethylases (KDMs), enzymes that remove the methyl group(s) from a methylated lysine side chain (Fig. 1).…”
Section: H3k9mtsmentioning
confidence: 99%